Analysis of Ranitidine Hydrochloride Content in Drug X Samples Using A UV-Visible Spectrophotometry - Rosmainar, Lilis; Yanwerico, Manuel (Universitas Pendidikan Mandalika, 2024)
The development and progress of modern society cannot be separated from the availability of health medicines. Conventional medicinal products such as capsules and tablets are formulated to release active compounds immediately after consumption. Tablets are solid drug dosage forms consisting of one or more medicinal ingredients. One type of solid drug dosage form is ranitidine hydrochloride. Ranitidine hydrochloride belongs to a class of antagonist drugs that attack histamine H receptors2 selectively and reversibly by reducing the process of secretion by gastric acid which is widely used for the treatment of stomach ulcers, intestinal ulcers (duodenum ulcers), Zollinger-Ellison syndrome, Gastro Esophageal Reflux Disease (GERD) and esophageal erosion. Determination of ranitidine hydrochloride levels was carried out using an ultraviolet spectrophotometer validation method with maximum absorption at a wavelength of ±314 nm. In UV spectrophotometer analysis, peaks were detected at wave number 313.80 nm with absorbance values of 0.425, 0.416, 0.421, 0.424, 0.413, and 0.418. The concentration results obtained for each sample were sample I 119.22%, sample II 116.70%, sample III 118.10%, sample IV 118.94%, sample V 115.85%, and sample VI 117.26% which fulfilled the requirements.